PEMANFAATAN YOUTUBE CHANNEL COCOMELON SEBAGAI MEDIA PENGENALAN KOSA KATA BAHASA INGGRIS ANAK - Miratul Hayati; Raihana Fibri Rahimia; Faza Karimatul Akhlak , (Universitas Al-Hikmah Indonesia, 2021)
The purpose of this study is to explain the use of YouTube channel Cocomelon as a medium for mastery of vocabulary for children aged 4-6 years in Karang Tengah village. This study uses a mixed method, the type of Explanatory Design. The subjects in this study were children aged 4-6 years who live in Karang Tengah Village, Tangerang and their parents who accompany their children to watch YouTube Cocomelon. The sampling technique was nonprobabillity sampling, using purposive sampling type. Collecting data using interview instruments, documentation and non-test instruments. Data analysis used Miles and Huberman's model and descriptive statistics. Based on the results of a questionnaire calculation related to the use of the Cocomelon YouTube Channel as a medium for introducing English vocabulary for children aged 4-6 years in Karang Tengah District, Tangerang, they are included in the